Correlation Between Proof of Work and Community Features in PMM Programs on Preschool Teachers' Pedagogical Competence - Suryani, Lilis; Anggrayni , Rice (UNIB Press, 2025)
Kurikulum Merdeka requires every teacher to develop themselves in providing a comfortable and enjoyable learning process. As a form of support for its implementation, the Ministry of Education, Culture, Research, and Technology provides a platform known as Platform Merdeka Mengajar (PMM). The utilization of PMM has become a necessity for every early childhood educator to enhance their pedagogical competencies through various available features. The aim of this research is to identify the relationship between Bukti Karya feature and Komunitas feature on PMM in developing the pedagogical competence of early childhood education teachers. The research uses a correlational quantitative approach and was conducted from March to July 2024. The sample consists of 45 teachers from Sekolah Penggerak TK/PAUD Batch 3 Kabupaten Bekasi in the Bekasi Regency. Data was collected from using a likert scale questionnaire via google forms. Validity testing was conducted by three experts, followed by a reliability test through a pilot study of the questionnaire. Data was analyzed using product-moment correlation and F-tests. The results indicate that the variables of Bukti Karya feature and Komunitas feature are simultaneously related to the variable of pedagogical competence.